Marker Assisted Selection for Common Bean Diseases Improvements in Tanzania: Prospects and Future Needs - Tryphone, George Muhamba; Chilagane, Luseko Amos; Protas, Deogracious; Kusolwa, Paul Mbogo; Nchimbi-Msolla, Susan (IntechOpen, 2013)
None